2022
DOI: 10.1590/1519-6984.260617
|View full text |Cite
|
Sign up to set email alerts
|

Colonization by Streptococcus pneumoniae among children in Porto Velho, Rondônia, Western Brazilian Amazon

Abstract: Streptococcus pneumoniae is one of the primary pathogens that are associated with acute respiratory infections (ARI) that cause high rates of morbidity and mortality among children under five years of age in developed and developing countries. This study aimed to determine the prevalence of nasopharyngeal colonization, the antimicrobial resistance profile, and the capacity for biofilm formation by S. pneumoniae isolated from children aged 0-6 years with ARI throughout the Porto Velho-RO. A total of 660 swabs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…These pathogens travel from the nasopharynx to the Eustachian tube and infect the middle ear which may result in OM (Coticchia et al, 2013;Mofatteh et al, 2018). It has also been reported that Streptococcus pneumoniae causes OM, acute respiratory infections, pneumonia, meningitis and sepsis (Silva et al, 2022). Depending on the type and severity, OM is treated differently, ranging from antibiotics to surgery (Lieberthal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These pathogens travel from the nasopharynx to the Eustachian tube and infect the middle ear which may result in OM (Coticchia et al, 2013;Mofatteh et al, 2018). It has also been reported that Streptococcus pneumoniae causes OM, acute respiratory infections, pneumonia, meningitis and sepsis (Silva et al, 2022). Depending on the type and severity, OM is treated differently, ranging from antibiotics to surgery (Lieberthal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%